PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TEKNIK SCRAMBLE UNTUK MENINGKATKAN HASIL BELAJAR PKn SISWA KELAS IV SDN 29 KEMBUNGLUAR KECAMATAN BANTAN - Rafizal, Rafizal; Syahrilfuddin, Syahrilfuddin; Lazim.N, Lazim.N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem of this research is the weakness of student’s learning result of PKn subject.It show from 20 student’s,12 student’s ( 45% ) have lower score,and it is only 8 student’s ( 60% ) have average score 63,50.The KKM of this school is 67.According to that problem,the research by implementing cooperative learning technic scramble teaching.In cycle I,the percentage of theacher activity in first meeting is adquate 58,33%.In second meeting, teacher activity significantly increased to 66,66% with good category.In cycle 2,first meeting was in good category 79,16% and second meeting indicated a very good category 87,50%.Meanwhile,the activity of student’s also improved.In cycle I indicated 54,16% in adequate category and in cycle 2 has increased up to 62,50% with good category.In cycle 2,first meeting,the activity of student’s has been increasing to 75,00% with good category and second meeting indicated very good category 83,33%.An average score of student’s learning result before implementation is 63.50% . It increased to 65,75% in cycle I,and 71,21 incylce 2.In implementation cooperative lerning technic scramble teaching can improve student’s learning result of fourth grade students of SD Negeri 29 Kembungluar in PKn subject.Key words: Cooperative technic scramble teaching, learning result of PKn subject.